Geomechanical Characteristics and Stimulation of Dibei Deep Tight Sandstone Reservoirs in the Kuqa Depression of Tarim Basin - Ke Xu; Haijun Yang; Hui Zhang; Zhimin Wang; Lu Fang; Guoqing Yin; Haiying Wang (Geofluids)
Facing the problem of increased production of deep tight gas reservoirs, this study takes the Dibei gas reservoir in Tarim Basin as an example, carries out geomechanical research, and reveals the rock mechanical properties, in situ stress, and fracture characteristics of the tight reservoir. From the perspective of the in situ stress field and the effectiveness of fractures, the study reveals their impacts on reservoir quality, wellbore stability, and fracturing networks. The results show that the in situ stress and the effectiveness of fracture mechanics under its control have obvious control over the production capacity in the Dibei gas reservoir. The positions and intervals with low in situ stress, high fracture density, and fracture effectiveness are often favorable parts. A directional well has the dual advantages of overcoming reservoir heterogeneity and safety and stability. Understanding the geomechanical characteristics can quantitatively optimize the best wellbore trajectory, reduce the difficulty of fracturing from the source of well location deployment, improve the efficiency of hydraulic fracturing, and then realize the stimulation of gas reservoirs. In addition, the favorable borehole trajectory considers both the sweet spot penetration and borehole wall stability, which will reduce the difficulty of fracturing and is conducive to the efficient stimulation of tight gas reservoirs. Geomechanics research has built an integrated bridge between geology and engineering, which plays a significant role in increasing gas production.